VALIDITY OF WEEBLY-BASED NATURAL AND SOCIAL SCIENCE TEACHING MATERIALS FOR ELEMENTARY SCHOOL STUDENTS - Sri Wondiningsih; Tri Mulyono; Tity Kusrina (SOSIOEDUKASI, 2026)
The rapid development of digital technology has encouraged the creation of more interactive and accessible learning materials in elementary education, particularly for Integrated Natural and Social Sciences. However, many classroom materials remain conventional and less responsive to students’ learning characteristics. This study aimed to determine the validity of Weebly-based Natural and Social Sciences teaching materials for fourth-grade elementary school students. The research used a descriptive quantitative design with expert validation involving one media expert and one material expert. The instruments consisted of validation sheets covering content accuracy, material depth, contextual relevance, language clarity, conceptual presentation, visual design, navigation, accessibility, and interactivity. The data were analyzed using descriptive statistics and Aiken’s V to measure expert agreement. The results showed that the media expert validation obtained a total score of 138 with an average of 4.60, while the material expert validation obtained a total score of 134 with an average of 4.47. The Aiken’s V values were 0.90 for media and 0.87 for material, both indicating very high validity. These findings show that the developed Weebly-based teaching materials are highly feasible and appropriate for use as digital learning resources in elementary school. The study implies that Weebly can support the development of structured, interactive, and pedagogically relevant teaching materials that align with student needs and curriculum demands.